2006
DOI: 10.1089/dia.2006.8.67
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Insulin Deprivation in Continuous Subcutaneous Insulin Infusion-Treated Patients with Type 1 Diabetes

Abstract: The dynamic evaluation of changes of capillary 3betaOHB levels can represent a useful support to home BG monitoring in the event of CSII interruption, providing faster information on early metabolic deterioration due to insulin deprivation and allowing preventative action for avoiding the evolution towards overt diabetic ketoacidosis. After reintroduction of insulin infusion the monitoring of the faster recovery of 3betaOHB relative to BG can provide useful information for the prevention of late hypoglycemia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…It would also be unlikely using the current protocol that the duration of hypoglycemia would be long enough to result in a severe hypoglycemic episode. Previous studies have shown that suspension of insulin delivery for up to 2 h has not resulted in significant ketosis (10,2125). In our studies, there was mild ketosis on four occasions when the pump was suspended for 90–180 min, and in each instance serum ketone levels returned to normal with the reinstitution of basal insulin therapy.…”
Section: Discussionmentioning
confidence: 98%
“…It would also be unlikely using the current protocol that the duration of hypoglycemia would be long enough to result in a severe hypoglycemic episode. Previous studies have shown that suspension of insulin delivery for up to 2 h has not resulted in significant ketosis (10,2125). In our studies, there was mild ketosis on four occasions when the pump was suspended for 90–180 min, and in each instance serum ketone levels returned to normal with the reinstitution of basal insulin therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Our finding of infrequent ketonemia following pump suspension is consistent with prior studies that have shown that pump insulin delivery can be suspended for up to 5 h without producing significant ketonemia. [7][8][9] In studies of sensor-augmented pumps with a low glucose suspend feature (Paradigm VeoÔ; Medtronic Diabetes), no significant ketosis or ketoacidosis has been reported in thousands of 2-h nocturnal pump suspensions. [10][11][12][13] On intervention nights (algorithm operational), glucose levels tended to be lower on nights with pump suspension compared with nights without pump suspension, reflecting that there were lower glucose levels on nights triggering a suspension.…”
Section: Discussionmentioning
confidence: 99%
“…They investigated the validity of laboratory ketone measurement as a diagnostic tool in DKA. As already described, handheld ketone meters have been shown to be accurate when compared with laboratory methods between 0 and 3 mmol/l 4 13 16. The cut-off used for diagnosis of DKA was a β-HB ≥3 mmol/l, as this correlated well with a bicarbonate level ≤18 mEq/l, which features alongside cut-offs for pH, anion gap and glucose concentration in the DKA diagnostic consensus criteria in adults 17.…”
Section: Indications and Limitationsmentioning
confidence: 73%
“…In one study,16 eight adult type 1 diabetic patients underwent interruption of continuous subcutaneous insulin infusion (CSII) therapy. Mean capillary β-HB levels rose more rapidly than plasma glucose levels on CSII interruption (p<0.05), and fell more rapidly on reinstating CSII (p=0.03).…”
Section: Indications and Limitationsmentioning
confidence: 99%